How to do comparative theology - Clooney, Francis X.; Stosch, Klaus von (Comparative Theology: Thinking Across Traditions Ser, 2018)
How To Do Comparative Theology clarifies method in comparative theology, dialogical learning, showcasing scholars doing theological work interreligiously. The group is diverse by age and stage of career, gender, religions studied, location in the United States and Europe. Yet the essays manifest coherence in intent, commitment to learning from the other, and confidence regarding the benefits of the questions and challenges arising